Rancang Bangun Aplikasi Point of Sale pada Kedai Kopi Elemen Kopi Berbasis Web - Steven Sanjaya Putra; Rosa Delima; Matahari Bhakti Nendya (Fakultas Teknologi Informasi, 2023)
The rapid development of the times has caused all aspects of life to always involve technology. With the rapid development of technology, of course it has positive and negative impacts. The positive impact that can be felt is that technology increases the effectiveness and efficiency of humans at work. One example is Point of Sale technology that can help humans in buying and selling transactions from both the customer and business owner sides.This web-based POS application is a computer software designed using the RAD method to help the owner of Elemen Kopi to record transactions, record stock items such as inventory and ingredients, employee management, make sales reports automatically and in real time. The problem faced was that before the existence of this POS application, Kedai Kopi Elemen Kopi still used a manual bookkeeping system that took a long time to record and was not computerized. This causes a high error rate that may occur. The purpose of designing this application is to provide an easy-used POS application to Kedai Kopi Elemen Kopi owners in recording accounting for both buying and selling transactions, expenditure and entry of goods. With this application, it is hoped that it can help record accounting and manage employees.